Tanggung Jawab Pidana Pelaku Kekerasan Seksual Yang Merupakan Penyandang Disabilitas Fisik - Permatasari, Dwi Ayu Widya (Peneliti.net, 2025)
Sexual violence crimes in Indonesia continue to increase over time. One significant example is the case of sexual violence committed by individuals with physical disabilities. This study aims to analyze the legal capacity and criminal responsibility of perpetrators with physical disabilities. This research uses a normative legal method with a statutory approach and literature study as the data collection technique. The findings show that persons with physical disabilities can still be held criminally responsible as long as the elements of sexual violence are fulfilled, including the act, its consequences, and the accompanying circumstances. A perpetrator with a physical disability may be prosecuted if the elements of “any person” as the subject, violence or threats of violence, coercion against a woman, and sexual intercourse outside of marriage by the perpetrator are proven. To address similar cases, it is expected that the government, the public, and law enforcement officials work together to provide better understanding of sexual violence crimes and to create a safe space for victims.